Las fiestas ciudadanas en el Reino de Quito (S. XVII). Apuntes para su estudio - Viforcos Marinas, María Isabel (Estudios humanísticos. Geografía, historia y arte, 1993)
This anide is an aproach to the study of the religions rejoicings in the Quito Kingdom. The bases are the Quito and Guayaquil town council actes between 1650-1657. Due the documental source we use, this work only is about the festivities under the auspices of the colonial authorities.